Inflammatory monocyte/macrophage modulation by liposome-entrapped spironolactone ameliorates acute lung injury in mice. (June 2016) - Ji, Wen-Jie; Ma, Yong-Qiang; Zhang, Xin; Zhang, Li; Zhang, Yi-Dan; Su, Cheng-Cheng; Xiang, Guo-An; Zhang, Mei-Ping; Lin, Zhi-Chun; Wei, Lu-Qing; Wang, Peizhong P; Zhang, Zhuoli; et al.
Aim: To examine the therapeutic/preventive potential of liposome-encapsulated spironolactone (SP; Lipo-SP) for acute lung injury (ALI) and fibrosis.Materials & methods: Lipo-SP was prepared by the film-ultrasonic method, and physicochemical and pharmacokinetic characterized for oral administration (10 and 20 mg/kg for SP-loaded liposome; 20 mg/kg for free SP) in a mouse model bleomycin-induced ALI.Results: Lipo-SP enhanced bioavailability of SP with significant amelioration in lung pathology. Mechanistically, SP-mediated mineralocorticoid receptor antagonism contributes to inflammatory monocyte/macrophage modulation via an inhibitory effect on Ly6C hi monocytosis-directed M2 polarization of alveolar macrophages. Moreover, Lipo-SP at lower dose (10 mg/kg) exhibited more improvement in body weight gain.Conclusion : Our data highlight Lipo-SP as a promising approach with therapeutic/preventive potential for ALI and fibrosis.